Medication Adherence of DPP-4 Inhibitors in Type 2 Diabetic Management: A Hill Bone Medication Adherence Scale Analysis - Kaliyan, Menaka; Palaniappan, Senthilkumar (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The management of diabetes is a global health challenge. Non-adherence to medication in chronic diabetics is a severe issue that is linked to negative consequences, which can be related to various factors. The present study aims to evaluate the proportion of adherence to DPP-4 inhibitors with other Oral Hypoglycemic Agents (OHA) in type 2 diabetic management using hill bone medication adherence scale analysis. Materials and Methods: In this prospective interventional study, out of 1000 patients, 974 fulfilled the inclusion criteria and considered for the study. A Nine-item Hill Bone Medication Adherence Scale (HBMAS) was used for data collection. Adherence was classified as ‘poor or high’ based on the patient’s mean score. The data was analyzed using student t-tests and ANOVA. Results: At the beginning of the study, 49.85% patients had low adherence to DPP-4 inhibitors, while 50.2% had high adherence. Following counseling, the medication adherence increased to 69.6% at the end of the study. Based on demographic data such as sex, occupation and social habit, statistically did not have any impact on medication adherence, but other data like age, duration of diabetic history, family history, personal history, BMI and treatment regimen had a huge impact on the adherence to DPP4 inhibitors. Conclusion: It was found that various factors contributed to non-adherence towards the diabetic medication with DPP4 inhibitors, while the result of present study indicates that counseling of patients for adherence to their diabetic medication improves understanding of disease status and positive impact on medication adherence which eventually enhances quality of life.
Keywords: Gliptin; Non-adherence; Hill-Bone scale; Medication adherence; Type 2 diabetic; patients